The Habitat Suitability Modelling of Rhinoceros Hornbills (Buceros rhinoceros) in Java Island, Indonesia - Setiawan, Taufik; Prasetyo, Lilik Budi; Mulyani, Yeni A.; Jarulis (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
Rhinoceros hornbills (Buceros rhinoceros) are a bird species belonging to the Bucerotidae family, which is vulnerable based on the IUCN red list of species. This is due to habitat fragmentation, which reduced the Rhinoceros hornbill habitat on Java. Efforts and strategies are needed to maintain Rhinoceros hornbill habitats. Information on the suitability of the Rhinoceros hornbill habitat on Java Island is required to develop a Rhinoceros hornbill conservation strategy. This study aimed to determine a habitat suitability model that produces the highest accuracy, analyze hornbill habitat suitability, and identify environmental variables that affect the existence of rhinoceros hornbills. Habitat suitability models were processed using three algorithms: random forest, support vector regression, and MaxEnt. The data used to model habitat suitability were presence and environmental variables. The model was evaluated using various accuracy measures, namely overall accuracy, sensitivity (sn), specificity (sp), Area Under Curve (AUC), and kappa coefficient. The resultsof model processing showed that the random forest algorithm produced the highest average accuracy of 0.74. The most important environmental variables for the habitat suitability model were the distance from the road (16.62%), distance from the forest (12.73%), and land cover (12.47%). The habitat suitability model was divided into three classes: low suitability, covering 75,048 km2 (55.94%); medium suitability, covering 52,911 km2 (39.44%); and high suitability, covering 6,213 km2 (4.63%). The results of the habitat suitability model showed that the habitat suitability class was the smallest in the area.